A molecular roadmap of cellular reprogramming into iPS cells - Polo, Jose M. (2012)
Factor-induced reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) is inefficient, complicating mechanistic studies. Here, we studied defined intermediate cell populations poised to becoming iPSCs by genome-wide analyses. We show that induced pluripotency elicits two transcriptional waves, which are driven by c-Myc/Klf4 (first wave) and Oct4/Sox2/Klf4 (second wave). Cells that become refractory to reprogramming activate the first but fail to initiate the second transcriptional wave and can be rescued by elevated expression of all four factors. The establishment of bivalent domains occurs gradually after the first wave, while changes in DNA methylation take place after the second wave when cells acquire stable pluripotency. This integrative analysis allowed us to identify genes that act as roadblocks during reprogramming and surface markers that further enrich for cells prone to forming iPSCs. Collectively, our data offer new mechanistic insights into the nature and sequence of molecular events inherent to cellular reprogramming.